Exploring the Causal Relationships and Underlying Mechanisms of Genetically Linked Immune Cells with Hemorrhagic Stroke - Li, Qi; Shen, Yingjie; Yu, Zhao; Wang, Yaolou; Shen, Yongze; Guo, Chunmei; Gao, Shang; Yang, Hongge; Gao, Aili; Liang, Hongsheng (Current Neurovascular Research, 2025)
IntroductionHemorrhagic stroke is a severe disease that endangers human life and well-being, with unclear pathogenesis. Recent studies have found an association between the immune system and hemorrhagic stroke, but the causal relationship between them remains unclear. We aim to elucidate the causal relationships between immune cell traits and hemorrhagic stroke using Mendelian randomization (MR).MethodsWe collected genome-wide association studies (GWAS) summary statistics for 731 immune cell traits as exposures, and GWAS data for hemorrhagic stroke outcomes, including intracerebral hemorrhage (ICH), subarachnoid hemorrhage (SAH), and cerebral aneurysm (non-ruptured) (CA), from the FinnGen Consortium's R10 dataset. Five methods were employed to evaluate the causal relationships, with the primary method being the inverse-variance weighted (IVW) method. Sensitivity analyses were carried out to enhance the robustness. Subsequently, we performed multivariate MR analyses, including confounding variables. Additionally, reverse MR analyses were carried out. Ultimately, we conducted pathway and functional enrichment analyses.ResultsAfter univariate and multivariate MR analyses, we identified that the higher counts of herpesvirus entry mediator (HVEM) on effector memory (EM) CD4+ cells (OR=0.954, 95%CI:0.925-0.984, P=0.003, PFDR=0.120) were a protective factor for SAH, and the counts of forward scatter area (FSC-A) on plasmacytoid dendritic cells (DC) (OR=1.059, 95%CI:1.023-1.095, P=0.001, PFDR=0.066) were associated with an increased risk of CA. The reverse MR indicated that CA could significantly increase the effector memory (EM) DN (CD4-CD8-) AC counts. No significant pleiotropy or heterogeneity was calculated in the MR analyses. SNP annotation and enrichment analyses suggested possible mechanisms by which immune cells affect hemorrhagic stroke.DiscussionThe involvement of immune cells in the neuroinflammatory responses has been demonstrated in previous studies. Among the immune cell traits with a significant causal relationship to hemorrhagic stroke, higher levels of HVEM on EM CD4+ cells may inhibit further inflammatory progress by binding to corresponding receptors, thereby exerting a protective effect against SAH. Alterations in FSC-A values (a flow cytometry measure of cell size) of plasmacytoid dendritic cells may contribute to atherosclerosis through cascading reactions that ultimately lead to CA. In addition, based on existing studies, other immune cell traits and related pathways identified in this study may contribute to the prevention and treatment of hemorrhagic stroke, providing a reference for future research. Finally, this study has some limitations, including population specificity, the use of a relatively lenient significance threshold (P < 1 × 10-5), and potential bias from weak instrumental variables and pleiotropy.ConclusionThis study demonstrated the causal relationships between immune cell traits and hemorrhagic stroke, laying the foundation for understanding the underlying mechanisms.
Keywords: causal relationship